A new neopasiphaeine bee associated with flowers of Loasaceae (Hymenoptera: Colletidae: Actenosigynes) - Siriani-Oliveira, Samuel; Júnior, José Eustáquio Dos Santos; Schlindwein, Clemens; Almeida, Eduardo A. B. (Zootaxa, 2024)
The genus Actenosigynes includes two species, A. fulvoniger (Michener, 1989) and A. mantiqueirensis Silveira, 2009, both oligolectic on flowers of Blumenbachia (Loasaceae) in southern Brazil. We describe a third species, Actenosigynes silveirai Siriani-Oliveira, sp. n., and provide additional evidence to the suspected narrow host-plant specificity between bees of this genus and Loasaceae. This new species was only recorded to collect resources on flowers of Aosa, a genus closely related to Blumenbachia in the subfamily Loasoideae. We illustrate female and male specimens of the three species to offer a complete summary of the morphological variation within this modestly sized genus of Neopasiphaeinae, including photographs of male genitalia and associated metasomal sterna. Moreover, we provide an identification key for the three species of Actenosigynes and the first phylogenetic and dating estimate for these taxa. The genus diversified in southern South America during the Miocene-Pliocene, following a more ancient divergence associated with the orogenic events that separated its sister-genus, Torocolletes, west of the Andes. We dedicate this newly described species to Fernando A. Silveira for his contributions to research on Brazilian bee taxonomy and biology.